The effect of time pressure and ego depletion on young children’s helping behavior - Zha, Zihan; Chen, Chang; Zhang, Renyuan; Zhang, Wenjie (Frontiers in Psychology, 2025)
Based on the theory of limited cognitive resources and the dual-process theory, this study explores the mechanisms by which time pressure (an external factor) and ego depletion (an internal factor) affect helping behavior in children aged 4 to 6 years through two experiments. Experiment 1 (n = 153, M = 5.42 years, SD = 0.71) examined the impact of time pressure on children’s helping behavior, while Experiment 2 (n = 221, M = 5.41 years, SD = 0.76) investigated the role of ego depletion. The results revealed that both time pressure and ego depletion significantly inhibited children’s helping behavior, with notable age-related differences in these effects: the helping behavior of 4- and 5-year-old children was significantly reduced under conditions of time pressure and resource depletion, whereas 6-year-old children demonstrated greater resistance to these disruptions. These findings suggest that children’s helping behavior relies more on the cognitive processing of the deliberative system rather than the automatic responses of the intuitive system. Furthermore, as children grow older, they gradually develop more effective cognitive resource regulation abilities to counteract the negative effects of resource depletion.